Anterior Cruciate Ligament Reconstruction Under 18 Years-Old: Functional Level and Sports Activity - MARQUES, Catarina F.; Figueiredo, Pedro; BRANCO, João; PINHEIRO, João (International Journal of Innovative Research in Medical Science, 2024)
Introduction: Reconstruction of the anterior cruciate ligament (ACL) in patients under 18 years-old has grown in last decades. Knee ligament rehabilitation aims to normalize functionality and promote a safe return to exercise and sports. This study intends to evaluate the functional capacity, the perception of quality of life and the level of activity, between 18 and 72 months after reconstruction of the ACL, in a population under 18 years old. Methods: Cross-sectional observational study that included a sample of young patients submitted to surgical reconstruction of the ACL. Patients underwent a rehabilitation program and were evaluated between 18 and 72 months after reconstruction. Metric tools were the Knee Outcome Survey - Activities of Daily Living Scale (KOS-ADLS), Short Form (SF)-36 (SF-36) and Tegner Activity Scale (TAS). Descriptive and correlation statistics (Pearson's and Spearman's Correlation Coefficients) were used. Results: This sample included 30 participants, 15 males and 15 females with a mean age of 19.4 ± 2.0 years and a mean postoperative time of 43.0 ± 16.8 months. In 20 patients, meniscus and cartilage injuries were identified. They had a pre-injury TAS of 8.0 ± 1.2 and a current TAS of 4.6 ± 2.2. They currently present KOS-ADLS score of 87.6 ± 11.0 and in the SF-36 vitality, mental health, and general health domains respectively 66.3 ± 22.9, 75.9 ± 19.9 and 75.5 ± 20.0. Conclusion: Patients under 18 years old undergoing ACL reconstruction have a high perception of knee functionality and quality of life. However, after the rehabilitation program, they significantly lower the level of sports activity. Meniscus and cartilage injuries negatively may affect functional capacity.